2020
DOI: 10.1039/d0ta08018g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and stable operation of nonfullerene organic solar cells: retaining a high built-in potential

Abstract: Modification of the HTL helps to attain a high built-in potential (V0) across the BHJ by suppressing the interfacial reaction at the HTL/BHJ interface. It is critical to retain a high and steady V0 to obtain efficient and stable nonfullerene OSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…A recent study reported that chemical reaction can occur between PEI (also PEIE) and ITIC molecules, which is also likely in part to be linked to the interfacial reaction caused by the PEDOT:PSS. [ 67–69 ] When PEI makes contact with ITIC, PEI can act as a nucleophile with the carbonyl (CO) groups in INCN, causing the structural change of ITIC and breaking intramolecular π‐electron overlap within the molecule ( Figure 5 a). The bleaching of the absorption peak and concomitant color change reflects the degradation of the electronic structure of ITIC.…”
Section: Recent Progress In Device Performancementioning
confidence: 99%
“…A recent study reported that chemical reaction can occur between PEI (also PEIE) and ITIC molecules, which is also likely in part to be linked to the interfacial reaction caused by the PEDOT:PSS. [ 67–69 ] When PEI makes contact with ITIC, PEI can act as a nucleophile with the carbonyl (CO) groups in INCN, causing the structural change of ITIC and breaking intramolecular π‐electron overlap within the molecule ( Figure 5 a). The bleaching of the absorption peak and concomitant color change reflects the degradation of the electronic structure of ITIC.…”
Section: Recent Progress In Device Performancementioning
confidence: 99%
“…The factors that contribute to the reduction in operational efficiency of OPV cells and modules over time are several and have been clearly identified. [320][321][322][323][324][325][326][327][328][329] Degradation factors that are common to all OPV devices include: photochemical and photo physical degradation of the active layer materials and interfaces; [330][331][332] morphological degradation [333,334] due to high thermal stress under operation; as well as, a series of degradation events that can be initiated by the ingress of H 2 O and O 2 in poorly sealed devices. [335][336][337] Additionally, there are some degradation factors specific to OPV modules, including electrical stress [338] and degradation at the cell interconnections.…”
Section: Encapsulation and Stability Testing Of Large Area Devicesmentioning
confidence: 99%
“…At the present stage, the fundamental identification and understanding of the underlying degradation mechanisms fairly lag behind that of the efficiency development, which originates from the mainstream material design rules and optimization strategies primarily dedicating to PCE enhancement instead of boosting stability. [ 15–17 ] Generally speaking, the inherent instability such as the changes of bulk‐heterojunction (BHJ) morphology and intrinsic attenuation of donor/acceptor (D/A) materials normally occur in the photoactive layers without the influence of the extrinsic factors. [ 18–20 ] Especially, the slow evolution from the initially optimal BHJ morphologies at metastable state to thermodynamically steady case at equilibrium, the aggregation and/or crystallization of NFAs, and the D/A demixing will induce the severe degradation of exciton dissociation, subsequent charge carrier transport, and extraction and give rise to the serious non‐radiative recombination, thereby shortening the lifetime of OPV devices.…”
Section: Introductionmentioning
confidence: 99%